2020
DOI: 10.1002/ece3.6798
|View full text |Cite
|
Sign up to set email alerts
|

Faunal input at host plants: Can camel thorn trees use nutrients imported by resident sociable weavers?

Abstract: “Islands of fertility” result from the focussing of water and nutrients around many shrub or tree species due to plants foraging for resources. Plant–animal feedbacks may amplify the development of such islands through environmental modification due to, for example, faunal deposition of nutrients and seeds. Fauna residing within vegetation clumps are likely to exert stronger feedbacks on their hosts than itinerant species. We studied the interaction between camel thorn trees ( Vachellia erioloba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Larger colonies may host hundreds of individual birds and nest chambers provide insulation, a crucial resource in arid environments, for its occupants (Lowney et al, 2020). Soils directly below colonies have particularly increased nutrient levels (Prayag et al, 2020) and this could result in direct effects on the local vegetation and animals. Weaver colonies have been shown to act as a resource to multiple species within the environment (Bolopo et al, 2019; Lowney & Charlton, 2017; Maclean, 1970; Rehn, 1965; Rymer et al, 2014) and maintain this impact throughout the year (Lowney & Thomson, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger colonies may host hundreds of individual birds and nest chambers provide insulation, a crucial resource in arid environments, for its occupants (Lowney et al, 2020). Soils directly below colonies have particularly increased nutrient levels (Prayag et al, 2020) and this could result in direct effects on the local vegetation and animals. Weaver colonies have been shown to act as a resource to multiple species within the environment (Bolopo et al, 2019; Lowney & Charlton, 2017; Maclean, 1970; Rehn, 1965; Rymer et al, 2014) and maintain this impact throughout the year (Lowney & Thomson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most species that use weaver colonies are not obligate associates and can exhibit behavioural plasticity in their use of weaver colonies. We hypothesize that because invertebrate abundance is influenced by organic matter (Noy‐Meir, 1985) and this collects below colonies (Prayag et al, 2020), that a greater abundance of invertebrates will be observed at colony trees than the control trees. We also hypothesize that due to thermal insulation against hot and cold temperatures that colonies provide (Lowney et al, 2020) and increased resources in terms of invertebrate abundance, small‐ to medium‐sized birds and reptiles will associate with colony trees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nesting chambers provide thermal benefits to occupants (Lowney, Bolopo, et al., 2020), a potentially crucial resource in arid environments. Food and nutrient resources may also concentrate at nest colonies, with soils below colonies massively enriched with nutrients (Prayag et al., 2020) that could have knock‐on effects on vegetation and animals in the local environment. Anecdotal data suggest a wide range of non‐obligate species also associate with these colonies (Maclean, 1973a).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesised that weaver colonies act as an important resource for multiple taxa due to the abiotic and biotic resources provided and we expected to observe more species, individuals and greater diversity at trees containing a colony and trees without a colony (control). We also hypothesised that colonies will provide different resources for different taxa; large mammals will use the structures for shade, whereas herbivores are likely to forage more at colony trees due to the nutrient‐rich vegetation and increased foliar biomass (Prayag et al., 2020). We also expected higher diversity of bird species associated with colony trees; large birds may use the top of colonies for nesting and perching, whereas small‐ to medium‐sized birds will likely use nesting chambers as a refuge from predators and to gain thermal isolation against hot and cold temperatures (Lowney, Bolopo, et al., 2020; Maclean, 1973a).…”
Section: Introductionmentioning
confidence: 99%